Hydrochemistry Of Dissolved Metals In Yamuna River Around Industrial Hub Of Himachal Pradesh, India (Applied Biological Research, 2015)
The Yamuna river flows through Sirmour district in Himachal Pradesh  (India) and receives domestic and industrial effluents from different villages and Ponta-sahib industrial hub situated on its bank. Ninety six surface water samples were collected from eight sites from the river  during 2014 and 2015. Water quality with respect to 9 heavy metals (Cr,  Cu, As, Cd, Ni, Pb, Mn, Zn & Fe) and 3 non-metals (NO3, Mg & Ca) was  assessed for their variations, source apportionment and pollution  indexing. Principal component analysis (PCA) outcome of different  factors indicated natural and anthropogenic activities as contributing  factors for metals profusion in the river. During 2014, three principal  components were identified to beresponsible for river water  deterioration and accounted for 94.73% of overall total variance. PCA1 in 2014 accounted for 70.16% of total variance and was characterized by high loading for Cr, Cu, NO3, As, Mn, Zn, Fe, Mg and Ca. River stretch  during 2015 showed high pollution load and two principal components  were identified responsible for the impairment of river water which  accounted for 88.67% of the overall total variance. PCA1 in 2015  accounted for 75.74% total variance and registered high loading for Cr,  Cu, As, Ni, Mn, Zn, Fe, Mg and Ca. Based on pooled pollution index, in  river water Cr, As and Zn were seriously (24.74), moderately (0.616)  and slightly (0.380) polluting metals, respectively. Although river quality  does not pose any serious threat to human health still various activities  domiciledat downstream need tobe discontinued to restore water quality.
Keywords: Dissolved metals; pollution index; principal component analysis; Yamuna